The Relationship Between Training And The Success Of Micro Small And Medium Enterprises Padang Selatan District Padang City - Ginting, Rezan; Irmawita, Irmawita (Universitas Negeri Padang, 2024)
This research is motivated by the low success of MSME business actors in South Padang District, Padang City, this is thought to be because training assessed in terms of training objectives, training methods and training implementation is still low. This research aims to reveal (1) a picture of training; (2) description of the success of MSMEs; (3) see the relationship between training and the success of MSMEs in Padang Selatan District, Padang City.This research uses a quantitative approach with a correlational type of research. The population in this study consisted of 60 respondents. The sampling technique uses cluster random sampling. The sample was taken from a population of 50 respondents, taking 85% of the total population. The data collection technique uses a questionnaire. Data analysis techniques use percentage formulas and product moment correlation formulas.The results of this research show that; (1) training for MSMEs in South Padang District is low; (2) the success of South Padang District MSMEs is still low; (3) there is a significant relationship between training and the success of MSMEs in South Padang District, Padang City. The researchers' suggestions are: 1) It is hoped that instructors can innovate regarding learning methods, training materials, facilities and infrastructure, training time, so that it can be good and appropriate training for business owners. 2) It is hoped that business actors will integrate entrepreneurship into every training material to support business success. 3) It is hoped that future researchers will be able to research new variables so that they can add to existing variables and complete them.